Exposure of Gender Equality through Children Stories for Students of Kranggan Lembur Mandiri Kindergarten, Jatirangga, Bekasi - Diyantari; Hasra, Hasnini; Widjayanti, Ellita Permata; Purbasari, Rahayu (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2021)
This community service activity aims to expose students to understanding the concept of gender and gender equality in order to minimize oppression, discrimination and bullying that mostly occurs against girls. This activity also aims to improve students' understanding of the value of character education and positive attitudes. The partner of this community development are students and teachers of Kranggan Lembur Mandiri Kindergarten, Jatirangga, Jatisampurna District, Bekasi. This community service activity is carried out through the method of assisting story reading, designing syllabus of story reading based on thematic reading, and providing material in the form of children's story books, as well as making children's story telling videos about gender equality, which can be used for students' independent learning. Monitoring and evaluation activities are carried out through observation and interviews. This activity helps improve students' understanding of the role and empowerment of women through education, enrichment of character and positive attitudes on gender justice (can work together, competence, active, empathize, problem solving), improve linguistic competence and visual literacy (recognition of colors and images), and also understanding of cultural literacy through children's stories containing local Indonesian culture and gender perspective.